Prevalence and impact of pelvic floor dysfunctions on quality of life in women 5–10 years after their first vaginal or caesarian delivery - Alba González-Timoneda; Nerea Valles-Murcia; Paula Muñoz Esteban; María Sol Torres López; Elisa Turrión Martínez; Patxi Errandonea Garcia; Lola Serrano Raya; Francisco Nohales Alfonso (Heliyon)
Background: Pelvic floor dysfunction (PFD) in women is a health problem with repercussions on quality of life. The literature agrees that PFD prevention strategies begin with identifying women who are most at risk of developing PFD in the future. However, recent evidence addressing its multifactorial origin is scant. Objective: Our aim was to investigate late prevalence, risk factors, and the impact on quality of life of PFD in women after their first vaginal or caesarian birth. Methods: We conducted an ambispective cohort observational study. Participants were primiparous women who had given birth to only one child by vaginal delivery or cesarean section between 2012 and 2016. Exposure and response variables, assessed using the International Consultation on Incontinence Questionnaire and the Pelvic Floor Distress Inventory, were collected during a phone interview 5–10 years after childbirth. Pearson's Chi-square, Student's t-test and odds ratio (OR) with their respective 95 % confidence intervals (CI) were calculated. Findings: A total of 456 women were included in the study. Overall, 50 % of the women had 1 or more PFD within 10 years of giving birth, while 43.9 % of women presented urinary incontinence, 5.5 % presented pelvic organ prolapse, and 15.6 % of women reported some type of anal incontinence. A third of the women perceived the symptoms as a dysfunction and a half of them reported mild or moderate symptoms. Conclusion: PFD in women is a prevalent and underdiagnosed problem. Our study advocates for early detection of PFD risk factors and emphasizes the need for increased visibility, awareness, and proactive health measures related to PFD.